Innowacyjność przedsiębiorstw branży spożywczej na tle ogólnych tendencji w latach 2002–2008 - Nieć, Melania; Klembowska, Dorota (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The aim of this article is to present result of the research concerning polish enterprises in food sector in innovativeness area. The research period include time before polish accessing to EU till 2008. In particularly pay attention on: innovation activity, expenditures on innovation, factors hampering innovation totally and especially in food and beverages sector.